THE 1988 FEDERAL CONSTITUTION FRAMEWORK AND THE LEGAL RECOGNITION OF THE IDENTITY DIFFERENCES IN BRAZIL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The present article has the objective to examine the legal recognition trajectory of the identity differences in Brazil in the light of the normative and principiological landmark inaugurated by the 1988 Federal Constitution. Therefore, initially, the study traces brief notes about the Brazilian constitutional history, then presents reflections on the democratic and plural horizon founded by the 1988 Major Law. Finally, it explores the legal recognition trajectory of the identity differences in the three decades of Citizen's Constitution, from the discussion of laws and judicial decisions, especially in the Federal Supreme Court. In the methodology, the study was based on the bibliographic research technique, the deductive reasoning mode, and the hermeneutic approach method.